Cellular and synaptic specializations for sub-millisecond precision in the mammalian auditory brainstem - Keine, Christian; Englitz, Bernhard (Frontiers in Cellular Neuroscience, 2025)
Audition in all animals relies on delicate sound pressure variations arriving at the ears, and these sound waves are intertwined representations of the complex auditory environment. The process of auditory perception and behavior is fundamentally based on reconstructive analysis, starting at the auditory nerve and culminating in the segregation of auditory sources through the extraction of spatial, spectral, and temporal cues. This analysis is made possible by specialized structures in the auditory brainstem that accurately represent and process incoming signals, preparing them for various downstream analyses. Decades of research have provided substantial insight into the morphological and physiological adaptations of specific auditory synapses, which we present and compare in the context of their presumed functions. Here, we focus on two parallel pathways originating from the auditory nerve and converging in the midbrain, featuring several well-studied synapses across multiple nuclei (cochlear nucleus, medial nucleus of the trapezoid body, ventral nucleus of the lateral lemniscus, and medial and lateral superior olivary nuclei). These synapses form the backbone of the high temporal precision of auditory representation, which is crucial for sound localization, speech comprehension, and speaker identification, each relying on subtle monaural or binaural cues. Finally, we highlight the similarities and differences with other brain areas that face challenges comparable to those of the auditory system.